Presence of Female Expert Comment Providers in Covid-19-related News in Bangladeshi Mainstream Newspapers - Meherun Nahar; Sanjoy Basak Partha; Tasnim Tabassum (CenRaPS Journal of Social Sciences, 2023)
The capacity of the media to influence political, social, and cultural practices and beliefs has grown beyond the scope of their role as information providers. When it comes to gender relations, the media not only reflects the realities of society but also contributes to its construction by highlighting misconceptions, inequalities, and perceived distinctions between women and men. However, studies reveal that news portrays a world in which women, especially as expert comment providers, are drastically underrepresented and rendered invisible as compared to men. This study examines how Bangladeshi mainstream media uses women as Covid-19 experts. Six national newspapers (The Daily Prothom Alo, The Daily Samakal, The Daily Ittefaq, The Daily Star, New Age, and The Asian Age) were evaluated to assess the situation. This study's data analysis from four months of each daily produced comparable findings to those of the global survey. Less than 10% of the specialists selected by the newspapers to offer their opinions in pieces about Covid-19 were female. In-depth interviews with the journalists were undertaken to uncover why fewer female experts' opinions are considered in the newspapers to address the problem more thoroughly.